Isolation, Identification, and Analyzing the Biological Characteristics of Pathogens Causing Stem Rot of Lanzhou Onion During Postharvest Storage and Studying the Influence of Pathogen Infection on the Active Components of Lanzhou Onion - Ruoxing Wang; Hui Zhang; Qingru Zhang; Jihui Xi; Kunhao Jiang; Jinzhu Li; Huali Xue; Yang Bi (Journal of Fungi)
This study was conducted in order to explore the pathogens that cause stem rot of fresh onions during postharvest storage, identify the incidence of stem rot, investigate the influence of pathogen infection on the active components of onion, and provide a theoretical basis for disease control during the postharvest storage of fresh onions. The pathogens were isolated and purified from the junction between the rotten and healthy tissues of onion stem rot that occurred naturally during storage at room temperature by tissue separation; then, the pathogens were identified by morphological and molecular biological techniques, the biological characteristics of the pathogens were analyzed, and finally, the influence of pathogen infection on the active ingredients of onion was studied. The results suggested that the main pathogens causing stem rot of fresh onions during postharvest storage were Talaromyces pinophilus, Trichoderma simmonsii, and Talaromyces minioluteus. The optimum colony growth conditions for T. pinophilus were as follows: a temperature of 30 °C, a pH of 7, light for 24 h, maltose as a carbon source, and peptone as a nitrogen source; the lethal temperature was 65 °C for 15 min. For T. simmonsii, the lethal temperature was 60 °C for 15 min, and the optimum sporulation conditions were a temperature of 25 °C, a pH of 5–7, light for 24 h, a carbon source of sucrose, and a nitrogen source of yeast powder. For T. minioluteus, the lethal condition was 65 °C for 15 min; the optimum colony growth conditions were a temperature of 25 °C, a pH of 8–9, 24 h of darkness, a carbon source of maltose, and a nitrogen source of peptone. The relative content of sulfur compounds, as the active components of onions, was much lower in the infected onions than in the healthy onions due to infection by the pathogens T. pinophilus, T.simmonsii, and T.minioluteus. This study will provide a theoretical basis for further effective control of the occurrence of postharvest stem rot diseases of onions.